2004
DOI: 10.1007/s11104-005-4884-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variations in carbon isotope discrimination, transpiration efficiency, and biomass production in rice as affected by soil water conditions and N

Abstract: Genotypic and environmental (soil water regime and N level) variation in carbon isotope discrimination (CID) in relation to the gas exchange, transpiration efficiency (A/T), and biomass production were investigated in field experiments using eleven rice (Oryza sativa L.) genotypes. The results showed that genotype was more dominant for variation in CID than in total biomass. Genotypic ranking in CID was consistent across environments because of small genotype × environment interactions. Japonica genotypes tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 42 publications
15
35
1
Order By: Relevance
“…Cheng et al (2004) have also found that as the N supply increases, the amounts of N in both free amino acids and proteins increase whereas the C/N ratio decreases. Water stress together with fertilization increased WUE (i.e., ␦ 13 C) in poplars, this result is consistent with previous studies (Brück et al, 2000;Welander and Ottosson, 2000;Li et al, 2003;Kondo et al, 2004) stating that WUE is significantly lower in well-watered treatments than in waterstressed treatments, but it increases with an increasing nutrient supply. As for the value of ␦ 13 C, the species effect was not significant.…”
Section: Tablesupporting
confidence: 92%
“…Cheng et al (2004) have also found that as the N supply increases, the amounts of N in both free amino acids and proteins increase whereas the C/N ratio decreases. Water stress together with fertilization increased WUE (i.e., ␦ 13 C) in poplars, this result is consistent with previous studies (Brück et al, 2000;Welander and Ottosson, 2000;Li et al, 2003;Kondo et al, 2004) stating that WUE is significantly lower in well-watered treatments than in waterstressed treatments, but it increases with an increasing nutrient supply. As for the value of ␦ 13 C, the species effect was not significant.…”
Section: Tablesupporting
confidence: 92%
“…30% FC, which were consistent with previous studies [50,51]. Additionally, Pn was negatively correlated with Rs and Rw (Fig.…”
supporting
confidence: 93%
“…Even though plant transpiration could affect the evaporation by altering the VPD inside the canopy, the effects were presumed to be small in this study because the pots were arranged sparsely enough and the experiments were conducted in the early growth period during which the pot was not fully covered by the canopy. Previous studies revealed the effects of stomatal conductance, leaf nitrogen and carbon content, and the ratio of intercellular to ambient CO 2 concentration (C i / C a ) on transpiration efficiency and P/T (Maruyama et al, 1985;Dingkuhn et al, 1989;Adachi et al, 1996) and also reported a negative correlation between P/T and carbon isotope discrimination (CID) (Dingkuhn et al, 1991;Kondo et al, 2004;Impa et al, 2005). However, CID showed a poor relationship with WUE, especially in the tillering period, and Zhao et al (2004) pointed out the possibility of breakdown of relationship between WUE and P/T to explain the poor relationship.…”
Section: Discussionmentioning
confidence: 99%